COMPREHENSIVE STUDY OF TWELVE PERCENT VALUE ADDED TAX INCREASE IN THE LIGHT OF LEGAL UTILITY THEORY AND HUMANISM COMMUNICATION THEORY - Farida Akbarina; Tania Dwika Putri; Syamsul Efendi; Heppi Syofya; Dian Indah Sari (ITB AAS Indonesia Surakarta, 2025)
Abstract This study is a qualitative study with a descriptive approach, namely an approach that describes one by one each main topic used in this article. The data used in this article is secondary data that researchers obtain from credible sources that are commonly used in each study. The data used is analyzed by the stages of data collection, data selection, data reduction, and drawing conclusions with more comprehensive research results below. The result in this article show that the policy of increasing the value added tax to twelve percent which is one of the legal products for luxury goods products can be in line with the objectives of Gustav Radbruch's law, namely justice and benefits if the allocation is correct and can be utilized as well as possible. Increasing the Value Added Tax to twelve percent can increase national income that can be allocated for national development, increasing community welfare, and increasing the human growth index. In the view of humanism communication theory if it is connected to the policy of increasing value added tax to twelve percent, the approach can be in line if only the utilization of the increase can be utilized as well as possible and truly. The increase in value added tax can increase national income significantly. By increasing national income, it can also increase the welfare of society, national development, and improve the quality of human resources. Keywords: Tweleve Percent, Value Added Tax, Legal Utility Theory,Humanism Communication Theory